Populația feminină: modernizare și adaptare - Urse, Laureana (Calitatea Vieții, 2007)
There is a generalized concern for the problems of the feminine population nuanced according to the geographical, historical, economic and cultural contexts. The Romanian area is such a context. In the first part of this analysis, the analytical perspective is stated after a brief presentation of the Romanian feminine population using statistical data. Two complementary analytical perspectives are proposed: 1) the perspective that transcends the gender; 2) the perspective of particularization that admits the existence of peculiarities of the feminine population, peculiarities that do not require making a hierarchy, rather they require sequential complementarities between the two genders. Once the analytical perspectives have been stated, the author highlights the issues related to the modernization and adaptation of the feminine population of Romania throughout three historical periods: (pre-communism, communism and post-communism): general characteristics of the modernization during each of the three stages, coexistence of modernity and traditionalism, failures and assimilations of modernity. The analysis concludes with a presentation of the satisfactions/dissatisfactions of the feminine population of Romania towards its life, in general and sequential, as it resulted from the 2006 Diagnosis of the Quality of Life.